2011
DOI: 10.1038/ejcn.2011.141
|View full text |Cite
|
Sign up to set email alerts
|

A vegan or vegetarian diet substantially alters the human colonic faecal microbiota

Abstract: Background/Objectives: Consisting of B10 14 microbial cells, the intestinal microbiota represents the largest and the most complex microbial community inhabiting the human body. However, the influence of regular diets on the microbiota is widely unknown. Subjects/Methods: We examined faecal samples of vegetarians (n ¼ 144), vegans (n ¼ 105) and an equal number of control subjects consuming ordinary omnivorous diet who were matched for age and gender. We used classical bacteriological isolation, identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
275
3
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(298 citation statements)
references
References 24 publications
10
275
3
10
Order By: Relevance
“…Lin et al reported that the gut microbiota of Bangladeshi children had higher bacterial diversity and an increased abundance of Prevotella relative to that of American children (18). Moreover, Zimmer et al compared fecal samples between vegetarians, vegans, and control subjects, and found that the abundance of Bacteroides and Bifidobacterium was significantly lower in vegetarians and vegans than in control subjects (19 Overall, these studies indicate that the Western diet of high fat, high protein, and low fi ber is associated with an increase in the Firmicutes/Bacteroidetes ratio. However, associations of nutritional factors such as micronutrients, macronutrients, and food groups with gut microbiota composition are still poorly understood (20).…”
mentioning
confidence: 99%
“…Lin et al reported that the gut microbiota of Bangladeshi children had higher bacterial diversity and an increased abundance of Prevotella relative to that of American children (18). Moreover, Zimmer et al compared fecal samples between vegetarians, vegans, and control subjects, and found that the abundance of Bacteroides and Bifidobacterium was significantly lower in vegetarians and vegans than in control subjects (19 Overall, these studies indicate that the Western diet of high fat, high protein, and low fi ber is associated with an increase in the Firmicutes/Bacteroidetes ratio. However, associations of nutritional factors such as micronutrients, macronutrients, and food groups with gut microbiota composition are still poorly understood (20).…”
mentioning
confidence: 99%
“…Omnivorous compared with vegetarian young Indian women displayed a weakly increased proportion of E. rectale (Kabeerdoss et al ., 2012). Germans on vegetarian or vegan diet showed a modest decrease in Bacteroides , Bifidobacterium and Escherichia coli compared with matched omnivores (Zimmer et al ., 2012). Vegetarians from Slovenia demonstrated a higher faecal concentration of the Bacteroides‐Prevotella group than omnivores (Matijašić et al ., 2014).…”
Section: Biome Engineering: Modifying the Nutrient Inputmentioning
confidence: 99%
“…174 and promote butyrate-producing Gram-positive bacteria such as E. rectale. 175 Similarly, subjects on a vegan or vegetarian diet showed significantly more acidic stool pH 89 and significantly lower fecal secondary bile acid production 83 than omnivores. Higher consumption of animal protein is one possible explanation of higher fecal pH value in an omnivorous diet, as proteolytic putrefactive bacteria are able to increase stool pH by producing alkaline metabolites.…”
Section: Microbiota Interactionsmentioning
confidence: 99%
“…The inconsistent findings from these studies might be due to the use of different experimental methods, the limited number of individuals in these studies, or poorly matched control groups. 89 The stool pH was lower among 250 subjects on strict vegan or vegetarian diets with equal numbers of age-and gender-matched control subjects compared to individuals consuming ordinary omniv- orous diets, and this likely inhibited the growth of E. coli and Enterobacteriaceae in vegetarian/vegan subjects. 89 Furthermore, it has been established that microbial− mammalian co-metabolites may be measured in urine that may provide information concerning intestinal microbial metabolic activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation